The Impact of Financial Literacy on Overconvidence and Investment Decision - Nur Hidayah (Jurnal Akuntan Publik, 2023)
Overconfidence and Investment Decision are very important instruments for individuals, especially investors in the capital market. Overconfidence is the first step if an individual wants to invest, because every investment instrument carries risks. If they have a confident attitude, they will dare to take risks. Investment decisions are very important in investment instruments. Individuals must be able to analyze portfolios by properly weighing risk and return. Overtrust and investment decisions must be determined by financial literacy, because if financial literacy is low, investors can become entangled in illegal investments. The purpose of this study is to empirically prove the effect of financial literacy on overconfidence and investment decisions. The sampling technique in this study used purposive sampling. Test the quality of the data used, namely test the validity and reliability test, test the model and test the hypothesis using multiple linear regression analysis. The results showed that the financial literacy variable had a positive and significant effect on overconfidence and investment decisions